Disulfiram chelated with copper promotes apoptosis in human breast cancer cells by impairing the mitochondria functions. Issue 6 (29th June 2016) - Yang, Yaping; Zhang, Kefan; Wang, Yawei; Li, Mengjia; Sun, Xiaoxue; Liang, Zhihong; Wang, Liwei; Chen, Lixin; Yang, Haifeng; Zhu, Linyan
Summary: Disulfiram (DSF) has been proved to have broad‐spectrum anti‐alcoholism effects, and it is also found to show stronger anti‐tumor effects after chelating with Cu 2+ to form DSF‐Cu complex. In this work, we studied the anti‐tumor activity of DSF‐Cu in MCF‐7 cells by flow cytometry, confocal laser scanning microscope, and atomic force microscopy to clarify the underlying anti‐tumor mechanisms. MCF‐7 cells were incubated with 50, 100, 150, 200, and 250 nM DSF chelated with 10 µM CuCl2 for 24 h. The results showed that DSF‐Cu could induce the accumulation of MCF‐7 cells in G2/M phase and apoptosis in a concentration‐dependent manner. Additionally, atomic force microscope (AFM) analysis at nanoscale level showed that the morphology of cell was significantly shrunk with destroyed filopodia and ultrastructure presented many irregular protuberances on the cell membrane after DSF‐Cu treatment, which was closely associated with the re‐arrangement of cytoskeleton. DSF‐Cu induced the production of reactive oxygen species (ROS), increased the concentration of intracellular Ca 2+ and decreased the mitochondrial membrane potential (MMP) in MCF‐7 cells resulting in a mitochondria‐dependent apoptosis pathway. The results indicated that DSF‐Cu has a potential anti‐tumor activity in breast cancer by impairing the mitochondria functions. SCANNING 38:825–836, 2016. © 2016 Wiley Periodicals, Inc.